2022
DOI: 10.1097/prs.0000000000009803
|View full text |Cite
|
Sign up to set email alerts
|

H-wing Neoumbilicoplasty: A New Technique for Advanced Abdominoplasty and Umbilical Zones by Gender

Abstract: Background: Multiple umbilicoplasty techniques have been described, even more after the advent of full tummy tuck procedures and the neoumbilicoplasty (X-shaped incision) described by the authors in a previous report. The authors decided to upgrade the technique (H-wing incision) because the former procedure is associated with relatively common complications. The authors report a case series of an upgraded technique for neoumbilicoplasty (H-wing technique), comparing its outcomes with their previous standard p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In other words, although useful, AU/ UC ratios are not the sole determinant of abdominal aesthetics. This notion is supported by Hoyos et al, 15,34 who advocated that a zone of umbilicus locations should be allowed after abdominal makeover.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In other words, although useful, AU/ UC ratios are not the sole determinant of abdominal aesthetics. This notion is supported by Hoyos et al, 15,34 who advocated that a zone of umbilicus locations should be allowed after abdominal makeover.…”
Section: Discussionmentioning
confidence: 90%
“…http://links.lww.com/PRSGO/C868.) 2,8,[10][11][12][13][14][15][16][17][18]23,24,31,[34][35][36][37] We advocate that standing AU/UC be used for visual guidance to gauge preoperative deficiencies and postoperative results, serving both patients and surgeons. At the same time, we also suggest that the XU/UP and UIC (standing) be used as feasible guides for surgical planning.…”
Section: Discussionmentioning
confidence: 99%
“…Ideal position has been debated for decades, and general consensus is still lacking. 6,10,17 Hoyos et al 7,8 reported that three localization modalities are mostly favored: (1) at 60% of the distance between the pubis and xiphoid process, measured from distal to proximal 24 ; (2) at the intersection between the midline and a line crossing both anterosuperior iliac spines 25 ; and (3) at a point located 15 cm above the pubic bone. 26 In many anatomical descriptions, the transumbilical plane is described at the level between the third and fourth lumbar vertebrae in the supine position regardless of gender.…”
Section: Discussionmentioning
confidence: 99%
“…5 If absent or not well-positioned, it can result in an unnatural looking abdomen. 2,4,[6][7][8][9] Despite that its physiological and aesthetic importance have long been recognized, the umbilicus was routinely discarded during surgery until the late 1950s. 10,11 With increasing appreciation of its importance in defining a harmonious anterior trunk, umbilical transposition performed toward the end of the surgery was described by Vernon in 1957.…”
Section: Introductionmentioning
confidence: 99%
“…4 Hoyos et al recently published the concept of the two-thirds to one-third umbilical position, by measuring the distance from the xiphoid to the pubis in abdominoplasties. 5 In DIEP flaps, the low transverse abdominal incision is usually marked in a location that will allow for dissection of the dominant perforator and for tension-free closure. Thus, the relation between the abdominal scar and the original umbilical site does not always follow the rules for umbilical transposition in abdominoplasties.…”
mentioning
confidence: 99%